2019 29th International Conference on Field Programmable Logic and Applications (FPL) 2019
DOI: 10.1109/fpl.2019.00066
|View full text |Cite
|
Sign up to set email alerts
|

Tinsel: A Manythread Overlay for FPGA Clusters

Abstract: Commodity FPGA boards with advanced networking facilities have great potential in the construction of highperformance compute clusters that scale. However, low-level design tools and long synthesis times are major barriers to productivity for application developers. In this paper, we explore the potential of a distributed soft-processor overlay, programmed in software at a high-level of abstraction, to deliver a useful level of performance for FPGA clusters. In particular, we demonstrate the use of hardware mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
(15 reference statements)
0
22
0
Order By: Relevance
“…3) A single-threaded x86 version, running on an Intel i9-7940X PC. This is only intended as a simple baseline; here, we do not compare the performance of our research platform against conventional compute clusters (some such comparisons can be found in a previous paper [5]). For the PR application, we reuse the implementation from the GAP benchmark suite [11].…”
Section: Benchmark Applications and Graphsmentioning
confidence: 99%
See 2 more Smart Citations
“…3) A single-threaded x86 version, running on an Intel i9-7940X PC. This is only intended as a simple baseline; here, we do not compare the performance of our research platform against conventional compute clusters (some such comparisons can be found in a previous paper [5]). For the PR application, we reuse the implementation from the GAP benchmark suite [11].…”
Section: Benchmark Applications and Graphsmentioning
confidence: 99%
“…This is the hypothesis of the POETS project (Partial Ordered Event Triggered Systems [4]), which forms the wider context for the work described in this paper. On the project, we have constructed a research platform consisting of a 48-FPGA cluster and a manycore RISC-V overlay called Tinsel [5] programmed on top. This serves both as a rapid prototyping environment for computer architecture research and, for certain applications, a genuine hardware accelerator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, processors consisting of larger numbers of far simpler cores, communicating by messagepassing or PGAS, can achieve more performance from a single chip, and scale more easily to large numbers of chips. This is the premise behind a number of recently developed manycore designs [1,2,3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…As part of a larger project, we have constructed a research platform consisting of a 48-FPGA cluster and a manycore RISC-V overlay programmed on top [7,9]. As well as providing a reconfigurable compute fabric, FPGAs also support a high degree of scalability due to advanced inter-chip networking capabilities.…”
Section: Introductionmentioning
confidence: 99%